The Role of Cyclin D1 and VEGF in Radiotherapy Response of Advance Stage Undifferentiated Nasopharyngeal Carcinoma - Nurhidayat, Ade Apon; Afiati, Afiati; Usman, Hermin Aminah; Hernowo, Bethy Suryawathy (Folia Medica Indonesiana, 2020)
Nasopharyngeal carcinoma has a high incidence and mortality rate in Southeast Asia and Indonesia. Radioresistance is a major obstacle to successful treatment of nasopharyngeal carcinoma. DNA repair in the cell cycle and angiogenesis factors affects the response of tumor cells to radiotherapy. Cyclin D1 that functions in the cell cycle process and VEGF as an angiogenesis factor are considered to play a role in the occurrence of radioresistance. The objective of this study is to find the association between immunoexpression of Cyclin D1 and VEGF with radiotherapy response in undifferentiated nasopharyngeal carcinoma. This study used a retrospective case control analysis design, secondary data from medical records of patients diagnosed as undifferentiated nasopharyngeal carcinoma who received complete radiotherapy at the Radiation Oncology Department Dr Hasan Sadikin Bandung were taken. There were 44 samples divided into radiosensitive (22 samples) and radioresistant (22 samples) groups. Immunohistochemical examination of Cyclin D1 and VEGF was performed on paraffin blocks of patients' biopsy. Data analysis using Chi-Square test (p â‰¤0.05) , OR 95% CI. Cyclin D1 expressed strongly in 86.4% of the radioresistant group and 59.1% in the radiosensitive group (p<0.05) and the OR 4,385 (0.993-19.356), VEGF was strongly expressed in 77.3% of the radioresistant group and 54.5% in the radiosensitive group (p>0.05). As conclusion, there were significant association between Cyclin D1 with radiotherapy respons in undifferentiated nasopharyngeal carcinoma. The stronger immunoexpression of Cyclin D1, the higher likelihood of radioresistancy. VEGF immunoexpression showed no significant association with radiotherapy response.